Considering New and Emerging Treatment Strategies for Depression: Beyond STAR*D and the Monoamines - McInnes, L. Alison; Marton, Tobias F (Current Psychiatry Research and Reviews, 2025)
While the number of treatment options for major depressive disorder (MDD) has grown in recent years, the lack of quality data to guide optimal modality selection has lessened the potential impact of having a more diverse set of mechanistic approaches to treatment. The last attempt to investigate treatment sequencing for MDD was the Sequenced Treatment Alternatives for Relief of Depression Study (STAR*D), which gave rise to the concept of treatment-resistant depression (TRD) as a failure to respond to two or more monoaminergic antidepressants. However, a recent reanalysis of the STAR*D data indicates that most patients do not remit even when treated with multiple traditional antidepressants. Given these new results, labeling the majority of patients as treatment-resistant is not appropriate or useful. If monoamine-based drugs are not that effective for the majority of MDD patients, then it is necessary to consider the mechanistically distinct pharmacological and non-pharmacological treatment options that have emerged recently, including brain stimulation, glutamate receptor modulators, and psychedelic medicines. While these new treatment modalities have the potential to enhance patient outcomes, clinicians and patients currently lack a framework to guide their choices other than cost, feasibility, personal preference, and certain medical contraindications. Here, we review alternative treatment modalities for monoamine non-responders and consider the possibility that there will be new first-line therapies for MDD. We will review how treatment decisions for these patients are currently being made and how developments in precision psychiatry may help guide rational treatment selection in the future.
Keywords: esketamine